1999
DOI: 10.1165/ajrcmb.20.2.3327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Anti-Interleukin-5 Monoclonal Antibody Treatment in a Murine Model of Pulmonary Inflammation

Abstract: The maturation of eosinophils in bone marrow, their migration to pulmonary tissue, and their subsequent degranulation and release of toxic granule proteins contributes to the pathophysiology observed in asthma. Interleukin-5 (IL-5) is essential for these processes to occur. Therefore, much emphasis has been placed on attempts to inhibit the production or activity of IL-5 in order to attenuate the inflammatory aspect of asthma. In this report, the immunological consequences of long-term exposure to an antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 28 publications
5
34
0
1
Order By: Relevance
“…We observed a remarkable persistence of the rat anti-mouse IL-4 in the serum of offspring of treated mother mice. These findings are similar to the long t 1/2 in mouse serum reported for rat anti-IL-5 (33). However, direct testing showed that 10-fold higher serum concentrations of anti-IL-4 were ineffective at blocking the susceptibility of newborn mice of allergic mothers to allergic sensitization, supporting an important mechanistic role for IL-4 at some point in the maternal/fetal interaction.…”
Section: Discussionsupporting
confidence: 82%
“…We observed a remarkable persistence of the rat anti-mouse IL-4 in the serum of offspring of treated mother mice. These findings are similar to the long t 1/2 in mouse serum reported for rat anti-IL-5 (33). However, direct testing showed that 10-fold higher serum concentrations of anti-IL-4 were ineffective at blocking the susceptibility of newborn mice of allergic mothers to allergic sensitization, supporting an important mechanistic role for IL-4 at some point in the maternal/fetal interaction.…”
Section: Discussionsupporting
confidence: 82%
“…Mice received 1 mg/kg intraperitoneal TRFK5, which provides prolonged bioactivity (37), in ''prevention'' (Days 0 and 8) and ''regression'' (Day 8) protocols, the latter aimed at therapy of established MPEs developing around Day 8 (13,38).…”
Section: Il-5 Neutralizationmentioning
confidence: 99%
“…Because T H 2 differentiation is IL-4-dependent, IL-4 neutralization may inhibit the development of T H 2 cells and the subsequent events that lead to allergic inflammation [9]. Also, as IL-4 induces IL-5 synthesis, IL-4 neutralization may also block IL-5-dependent pulmonary eosinophilia.…”
Section: Introductionmentioning
confidence: 99%